Analisis Persepsi Siswa dan Guru terhadap Implementasi Kurikulum Merdeka pada Pembelajaran PAI di MTS Tanada - Rifqiya Zahara; Hanifah Sabrina Aulia; Fathur Rohman (Bhinneka: Jurnal Bintang Pendidikan dan Bahasa, 2026)
In this study, it is planned to analyze teachers' and students' perceptions regarding the implementation of the Merdeka Curriculum at IRE classes in MTs Tanada. In terms of method used, this study is a qualitative study carried out with field studies in which methods of observation, interviews, and documentation are included. According to the findings obtained from the study, the Merdeka Curriculum has brought about changes in the process of PAI teaching in terms of active participation of students, using digital media in learning processes, discussion activities through the P5 process. While teachers see the Merdeka Curriculum as flexible and supportive of creative learning, students see the lessons taught within the scope of this curriculum as diverse and attractive. Although the implementation of the Merdeka Curriculum shows some positive aspects, it has also faced a number of challenges related to different understandings between teachers, regulations, difficulty in assessing attitudes, and the heavy workload of students. This study concluded that the implementation of the Merdeka Curriculum in Islamic Education in MTs Tanada was quite successful despite the need for improvements in teaching skills.